Understanding how survivors of non-consensual intimate image dissemination are perceived by UK and Norwegian respondents - Dean Fido; Anny C. Hesbøl; Anthony Danby (Acta Psychologica)
Purpose: In popular media, ‘revenge pornography’ refers to the non-consensual sharing of intimate images (NCSII) of another. Despite survivors of NCSII facing long-term consequences, they still face victim-blaming attitudes. Extant literature has typically sampled from countries where NCSII has long been illegal, such as the United Kingdom (UK); neglecting perspectives from countries lacking NCSII-specific legislation, such as Norway at the time of data collection. Methods: Participants (n = 477) from the UK and Norway responded to vignettes depicting NCSII, which differed by the survivor-perpetrator relationship depicted (i.e., casual vs. committed). Results: Controlling for participant sex and psychopathic personality traits (previously implicated in judgements of image-based sexual abuse), UK citizens perceived NCSII to have worse impacts on survivors than Norwegian citizens. Moreover, data trends suggested participants attributed increased victim-blame in vignettes featuring casual relationships, with higher self-reported psychopathic personality traits predicting judgements associated with viewing NCSII as less criminal in nature. Conclusion: These findings emphasise a need to better understand the role of legislation in public perceptions of NCSII (and image-based sexual abuse more broadly) and the need to be conscious about further exploring technology-facilitated crime internationally.